Evolving multidimensional transformations for symbolic regression with M3GP - Muñoz, Luis (2022)
Muñoz, L., Trujillo, L., Silva, S., Castelli, M., & Vanneschi, L. (2019). Evolving multidimensional transformations for symbolic regression with M3GP. Memetic computing, 11(2), 111–126. https://doi.org/10.1007/s12293-018-0274-5